Marital Social Skills and Marital Satisfaction of Women in Situations of Violence - Cardoso,Bruno Luiz Avelino (2019)
Abstract Marital Social Skills (MSS) are related to Marital Satisfaction (MS). However, abusive relationships present a deficit in the use of health strategies for conflict management and damages to those involved. This study evaluated in 23 women, with an average age of 35 years, in situations of intimate partner violence, the MSS, MS and the forms of violence suffered. For this, it used the MSS Inventory, MS Scale and a Violence Questionnaire. The results showed a predominance of psychological violence, a high level of marital dissatisfaction and a deficient repertoire of MSS. Negative correlation was identified between MSS, Proactive Self-Control and Marital Dissatisfaction; positive correlation between Assertive Conversation and Marital Dissatisfaction (and Marital Interaction) and negative correlation between Self-Assertiveness, Proactive Self-Control and situations of violence. Thus, the importance of specific MSS training for this population and the understanding of the nature of assertive responses in the sociocultural context is noted.